Determinants of six-minute step test performance in chronic obstructive pulmonary disease: a retrospective cross-sectional study - Aldair Darlan Santos-de-Araújo; Daniela Bassi-Dibai; Izadora Moraes Dourado; Nelson Francisco Serrão Júnior; Renan Shida Marinho; Paula Angélica Ricci; Cássia da Luz Goulart; Renata Gonçalves Mendes; Alessandra Adami; Audrey Borghi-Silva (Sport Sciences for Health, 2026)
Abstract Purpose The six-minute step test (6MST) is a valuable assessment to determine functional capacity in people with chronic obstructive pulmonary disease (COPD). However, clinical and behavioral variables, and personal characteristics, may be associated with test performance. No predictive equations are available that account for one or more of these variables in the estimation of functional capacity outcome from the 6MST. We sought to identify clinical and behavioral variables associated with 6MST outcome (total number of steps) in patients with COPD. Methods This retrospective analysis included 122 adults, aged ≥ 50 years, with stable COPD that underwent a 6MST test. Cohort was characterized by anthropometric, medical and smoking history, comorbidities, medications, lung function (spirometry), presence of dyspnea (modified medical research council scale; mMRC), echocardiography. Univariate and multivariate regression analyses, and 5-fold cross-validation, were performed to develop and internally validate an association-based model for 6MST. Results Univariate linear regression reported that age, forced expiratory volume in one second (FEV 1 ), forced vital capacity (FVC), FEV 1 /FVC, mMRC, type 2 diabetes mellitus, hypertension, chronic heart failure (CHF), inhaled corticosteroid, anticoagulants, beta-blockers, and diuretics were significantly associated with 6MST ( p < 0.05). Multiple regression analysis indicated that 43.2% of the variance in 6MST performance was associated with BMI, age, FEV 1 /FVC, current smoking status, presence of CHF and dyspnea (mMRC), and use of short-acting β-agonists (R 2 adjusted 0.432; p < 0.05). Conclusions Clinical and behavioral variables are associated with 6MST outcome. While warranting further confirmation, these findings contribute to better understanding multidimensional factors related to functional performance in COPD.